Competition and Certification: Theory and Evidence from the Audit Market - Geng, Heng (Griffin); Zhang, Cheng; Zhou, Frank S (The Review of Corporate Finance Studies, 2026)
We study how financial certifier competition influences loan contracting in the context of financial auditing. Exploiting the unexpected demise of Arthur Andersen that exogenously decreased auditor competition, we find a greater decrease in loan spread for borrowers in markets in which certifier competition declined more. Additional analyses suggest the result stems from enhanced audit quality and reduced credit risk. The effect of certifier competition is stronger for borrowers with weaker external monitoring and those generating significant revenue for their auditors. Our evidence highlights negative consequences of financial certifier competition. (JEL D43, G21, M42, M49)